Numerical simulation of aluminum alloy 6061 micro-mold fabrication for the production of polymeric microstructures by micro-hot-embossing - Chester, Shawn A. (2013)
Micro-molds play an important role in the manufacturing process of polymeric micro-devices, e.g. microfluidic devices, as they determine the product quality and the overall production cost. We report here the applicability of a large-deformation, high-temperature, isotropic elastic-viscoplasticity model for the prediction of micron-scale hot-embossing of AA6061. The material parameters in the constitutive model were determined by fitting the stress–strain curves from compression tests at various temperatures and strain rates. The constitutive theory was implemented in a finite element program, and the numerical simulation capability was validated by predicting the response of AA6061 in some representative macro-scale experiments; these experiments had not been used for the determination of the material parameters in the constitutive model. Additional micron-scale hot-embossing experiments on AA6061 were conducted, and by comparing the numerical simulation results to the corresponding physical experiments, we demonstrate that the deformation evolution of AA6061 during micro-hot-embossing is well predicted. The constitutive model and its numerical implementation open the possibility of optimizing the process of making micro-molds for microfluidic devices from AA6061.